In search of effective altruists. Issue 7 (7th February 2021) - Genç, Murat; Knowles, Stephen; Sullivan, Trudy
ABSTRACT: The effective altruism movement argues that people wanting to do the most good they can should donate to charities fighting poverty in poor countries overseas, rather than to charities helping people in need in wealthy countries. This is because there is greater need in the developing world meaning it is possible to save lives or improve living conditions at reasonably low cost. However, most people living in developed countries prefer to donate to charities helping people in need in their own country, rather than charities helping people in need in the developing world. This paper analyses why this might be. We conduct a discrete choice experiment to determine the relative importance people place on the effectiveness of a donation, the need of recipients, and whether the donation will be spent at home or overseas. We find that many people place more weight on where the donation will be spent than on how effective it will be. We also find that a significant number of people are not aware, or do not believe, a donation will be more effective in the developing world. In addition, many people's donation decisions are guided by emotion or intuition, rather than rational calculation.